AUP1 Regulates the Endoplasmic Reticulum-Associated Degradation and Polyubiquitination of NKCC2 - Nadia Frachon; Sylvie Demaretz; Elie Seaayfan; Lydia Chelbi; Dalal Bakhos-Douaihy; Kamel Laghmani (Cells, 2024)
Inactivating mutations of kidney Na-K-2Cl cotransporter NKCC2 lead to antenatal Bartter syndrome (BS) type 1, a life-threatening salt-losing tubulopathy. We previously reported that this serious inherited renal disease is linked to the endoplasmic reticulum-associated degradation (ERAD) pathway. The purpose of this work is to characterize further the ERAD machinery of NKCC2. Here, we report the identification of ancient ubiquitous protein 1 (AUP1) as a novel interactor of NKCC2 ER-resident form in renal cells. AUP1 is also an interactor of the ER lectin OS9, a key player in the ERAD of NKCC2. Similar to OS9, AUP1 co-expression decreased the amount of total NKCC2 protein by enhancing the ER retention and associated protein degradation of the cotransporter. Blocking the ERAD pathway with the proteasome inhibitor MG132 or the α-mannosidase inhibitor kifunensine fully abolished the AUP1 effect on NKCC2. Importantly, AUP1 knock-down or inhibition by overexpressing its dominant negative form strikingly decreased NKCC2 polyubiquitination and increased the protein level of the cotransporter. Interestingly, AUP1 co-expression produced a more profound impact on NKCC2 folding mutants. Moreover, AUP1 also interacted with the related kidney cotransporter NCC and downregulated its expression, strongly indicating that AUP1 is a common regulator of sodium-dependent chloride cotransporters. In conclusion, our data reveal the presence of an AUP1-mediated pathway enhancing the polyubiquitination and ERAD of NKCC2. The characterization and selective regulation of specific ERAD constituents of NKCC2 and its pathogenic mutants could open new avenues in the therapeutic strategies for type 1 BS treatment.